2014
DOI: 10.1103/physrevb.90.245120
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-protected topological states of interacting fermions and bosons

Abstract: We study the classification for a large class of interacting fermionic and bosonic symmetry protected topological (SPT) states, focusing on the cases where interaction reduces the classification of free fermion SPT states. We define a SPT state as whether or not it is separated from the trivial state through a bulk phase transition, which is a general definition applicable to SPT states with or without spatial symmetries. We show that in all dimensions short range interactions can reduce the classification of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
154
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(161 citation statements)
references
References 76 publications
7
154
0
Order By: Relevance
“…The first prominent example on deconfined quantum criticality is discovered by Senthil et al [19][20][21][22] in Mott insulator on square lattice. Deep in the Mott phase, the charge degree of freedom is frozen while the spin degree of freedom suffers from a variety of competing orders.…”
Section: A Phase Transition Between Neel and Vbs Order In Mott Insulmentioning
confidence: 99%
See 3 more Smart Citations
“…The first prominent example on deconfined quantum criticality is discovered by Senthil et al [19][20][21][22] in Mott insulator on square lattice. Deep in the Mott phase, the charge degree of freedom is frozen while the spin degree of freedom suffers from a variety of competing orders.…”
Section: A Phase Transition Between Neel and Vbs Order In Mott Insulmentioning
confidence: 99%
“…Each component of the rotor couples with the fermion bilinear and acts as a mass term. Once we integrating out the fermions, one obtains a Wess-Zumino-Witten theory for the fluctuating rotor 21,40,41 . The WZW term of the rotor originates from the special band structure of Weyl semimetal who contains monopole in momentum space around the Weyl points.…”
Section: A Phase Transition Between Neel and Vbs Order In Mott Insulmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism was discovered in the context of interacting topological insulators, it was found that some topological insulators/superconductors can be trivialized by interaction. Or in other words their boundary states, which without interaction are gapless Dirac fermions or Majorana fermions at one lower dimension, can be completely gapped out by interaction without topological degeneracy or condensing any fermion bilinear mass operator [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%